Surgical Experience of Transcranial Approaches to Large-to-Giant Pituitary Adenomas in Knosp Grade 4 - Guan, Xiudong; Wang, Yangyang; Zhang, Chengkai; Ma, Shunchang; Zhou, Wenjianlong; Jia, Guijun; Jia, Wang (Frontiers in Endocrinology, 2022)
Pituitary adenomas in the Knosp Grade 4 are difficult to resect completely and generally involved in poor prognosis, because of the closed relationship between the tumor and internal carotid. In this study, the authors retrospectively reviewed the outcome of different transcranial approaches in the management of large-to-giant pituitary adenomas in the Knosp Grade 4. A total of 42 patients with large-to-giant pituitary adenomas in the Knosp Grade 4, who underwent craniotomy in the Pituitary Disease Subdivision, Department of Neurosurgery, Beijing Tiantan Hospital between March 2012 and March 2015, were included in this study. Clinical characteristics, surgical methods, complications, and outcomes were evaluated. The median age was 45 years old (range, 19-73 years old), and 42.9% of enrolled cases were males. The mean tumor diameter was 43.6 mm, and the mean volume was 30.9 cm3. 26 patients underwent the frontolateral approach, while 16 cases accepted the frontotemporal approach. Gross-total resection was achieved in 11 patients (26.2%), near-total in 26 (61.9%), and subtotal in 5 (11.9%). The adenomas were larger, and the distance of the tumor extending to the lateral skull base was also further in the frontotemporal approach cases. Surgical time was shorter, and bleeding volume was less in the frontolateral approach cases. Subsaller extension was associated with incomplete resection in pituitary macroadenomas of the Knosp Grade 4. The craniotomy is still an effective treatment for pituitary macroadenomas in Knosp Grade 4.